PERANCANGAN SISTEM INFORMASI INVENTORY BARANG BERBASIS WEB PADA PT.HASANAH BUBUK SENTOSA - Wahyu Santoso; Samsoni (CV. Multi Kreasi Media, 2022)
This research explains about the problem of inventory items in warehouse division of PT. Hasanah Bubuk Sentosa, is still used the documentation data of output and input items seen by journal and items request directly. Thus it’s made performance of the company slower. The data are not integration and consolidation. Whereas, the system that will be made by the researcher based on the working system has been in warehouse division of PT. Hasanah Bubuk Sentosa. Another of inputting, outputting process and requesting items also this system full of features to make the report and find the data based on items name. Therefore, this system can be useful for the warehouse division of PT. Hasanah Bubuk Sentosa. In order to apply the planning, then used the Waterfall method as the trying system. Also this expected system can be hasten in inputting, outputting process and requesting items and making the report it can be helping for PT. Hasanah Bubuk Sentosa.